Seed Reproduction of Populus gamblei, Dode - Palit, S. (Indian Forester, 1980)
Although trials for vegetative propagation of Populus gamblei Dode have been carried out along with other poplars in the past, their success has so far been limited in West Bengal. Attempts at seed reproduction have also been largely unsuccessful. A fresh effort was, therefore, made to propagate this species from seeds, following the suggestions outlined by Dr. M. Viart, the French Silviculturist, in 1976. This paper discusses the nursery experiment findings, which have been quite encouraging. This success may, indeed, be deemed a break-through which promises to open up the possibilities of large scale field introduction of this fast growing and industrially important species.